2013
DOI: 10.1080/00223131.2013.852488
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of large negative reactivity of an accelerator-driven system in the Kyoto University Critical Assembly

Abstract: Large negative reactivity of a subcritical system driven by a pulsed 14 MeV neutron source has been measured in the Kyoto University Critical Assembly. The subcriticality of the accelerator-driven system (ADS) ranged in effective multiplication factor roughly from 0.98 to 0.92, which corresponded to an operational range of an actual ADS proposed by Japan Atomic Energy Agency. As the measurement technique, pulsed neutron method, power spectral analysis for pulsed neutron source, accelerator-beam trip method wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…The prompt-neutron decay constant could be determined from the former correlated component and the latter uncorrelated peak points, respectively, and these decay constants were consistent with that obtained by a pulsed neutron experiment. Following the above study, they also showed that the magnitude of the correlated reactor-noise component was reduced with an increase in subcriticality and eventually this component could be hardly observed [20].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…The prompt-neutron decay constant could be determined from the former correlated component and the latter uncorrelated peak points, respectively, and these decay constants were consistent with that obtained by a pulsed neutron experiment. Following the above study, they also showed that the magnitude of the correlated reactor-noise component was reduced with an increase in subcriticality and eventually this component could be hardly observed [20].…”
Section: Introductionmentioning
confidence: 93%
“…Adjacent to both axial sides of the active region of each fuel assembly, about 56 cm upper and 55 cm lower polyethylene reflectors were attached, respectively. A detailed view of the fuel assembly is given by Sakon et al [20]. The core was surrounded by polyethylenereflector assemblies.…”
Section: Description Of Kuca Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced concepts of FR cores have been proposed by several authors [29,30]. On ADSs, some fundamental research works have been carried out using an experimental facility [31,32].…”
Section: Tatsumi and G Chibamentioning
confidence: 99%
“…1. Notably, the 100 MeV protons generated from the FFAG accelerator were injected into a subcritical system under the following parameters: 30 pA beam intensity; 30 Hz repetition rate; 200 ns pulsed width; 1.0×10 7 1/s neutron yield. The calculated reaction rate was obtained by evaluating the volume tallies of activation foils.…”
Section: Mmentioning
confidence: 99%